Papel do receptor b2 de cininas após tratamento com capsaicina no bulbo de ratos - Franca, Camilla Estevao de [UNIFESP] (2016)
Kinins are neuropeptides involved in pain and inflammation process. They are activated by the release of two B1 and B2 receptors. The B2 receptor is considered a constitutive receptor in the central and peripheral tissues. the B1 receptor is generally absent in healthy animals or expressed in very low amount in a few tissues and cells. Capsaicin is a vanilloid receptor type 1 (TRV1), red pepper component participates in thermal transduction of pain and inflammation. The TRV1 cause degeneration of primary afferent fibers (C (A?)) which are sensory fibers that mediate pain. Objective: To demonstrate and localize the cinin B2 protein receptor in the central and peripheral nervous system of neonate and adult rats and determine if those receptors are original from the primary sensory C fibers and to analyze the genic expression of this receptor after capsaicin administration. Methods: Rats were treated with capsaicin in the second day of life (50mg/kg, subcutaneously) or two weeks prior the sacrifice (125 mg/kg for 3 days, subcutaneously). The receptor expression in the radioligante marcado isotopicamente sites was measured in tissue sections marked with the radioligand 125I-HPP-Hoe 140 (B2R) in the medulla, spinal cord and aorta. mRNA levels for B2R was measured by RT-PCR qualitative in the paratrigeminal nucleus (Pa5), solitary tract nucleus (NTS), spinal cord, liver and hypothalamus. Results: After treatment of the animals with capsaicin we could observe the location and B2 receptor expression in Pa5 and NTS as well as in the aorta and spinal cord, by autoradiography and, observe its expression by the analysis of gene expression also in the hypothalamus and liver. The B2 receptor levels of expression was not changed by the treatment with capsaicin in neonates as compared with controls in autoradiography, PCR in real and qualitative time. Conclusion: Suggest B2 kinin receptor not suffer influence afferent fibers capsaicin sensate may be different mechanisms for modulation.